Kebijakan Transportasi Masa Pandemi Covid-19 - Iskumaila Khoirunnisa; Mega Novetriskha Putri (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
This research discusses the issue of “Transportation Policy during PSBB and PPKM of Covid-19 Pandemic in DKI Jakarta from 2020 to 2021.” The purpose of the study is to analyze the pattern of transportation movement during PSBB and PPKM during Covid-19 pandemic. The method used was Quantitative Descriptive with correlation analysis technique using normality test and Kolmogorov-Smirnov tests. The study provided some variables; travel frequency, travel distance, travel time, travel intention, travel location, mode of transportation, and transportation cost rates. The result shows that there are four variables that changes during the implementation of PSBB and PPKM policies which are travel frequency, travel time, travel location, and transportation cost rates. There is a decrease in the frequency changes from very often to rare. For distance travel variable, there is a slight increase in mileage. For travel time variable, there is a decrease in the time span of more than 2 hours to 1 or 2 hours. As for the other variables; intent, location, mode of transportation, and cost fares, tend to have small changes.